To solve this equation, we will follow the steps:
1) Distribute 14 to the terms inside the parentheses:
2/3(x - 6) = 14(x - 6)
2) Multiply both sides of the equation by 3 to eliminate the fraction:
3 * 2/3(x - 6) = 3 * 14(x - 6)
2(x - 6) = 42(x - 6)
3) Distribute 2 to the terms inside the parentheses:
2x - 12 = 42x - 252
4) Subtract 2x from both sides to isolate the variable:
2x - 12 - 2x = 42x - 252 - 2x
-12 = 40x - 252
5) Add 252 to both sides of the equation:
-12 + 252 = 40x - 252 + 252
240 = 40x
6) Divide both sides by 40 to solve for x:
240/40 = 40x/40
6 = x
Therefore, the solution to the equation is x = 6.
Solve 2/3(x −6)=14(1 point)
Responses
−27
15
27
−15
3 answers
that is not an answer choice
Apologies for the confusion.
To solve the equation 2/3(x - 6) = 14, we will follow these steps:
1) Distribute 2/3 to the terms inside the parentheses:
(2/3) * (x - 6) = 14
2) Simplify the left side of the equation:
(2/3) * x - (2/3) * 6 = 14
(2/3)x - 4 = 14
3) Add 4 to both sides of the equation:
(2/3)x - 4 + 4 = 14 + 4
(2/3)x = 18
4) Multiply both sides by 3 to eliminate the fraction:
3 * (2/3)x = 18 * 3
2x = 54
5) Divide both sides by 2 to solve for x:
(2x)/2 = 54/2
x = 27
Therefore, the solution to the equation is x = 27.
To solve the equation 2/3(x - 6) = 14, we will follow these steps:
1) Distribute 2/3 to the terms inside the parentheses:
(2/3) * (x - 6) = 14
2) Simplify the left side of the equation:
(2/3) * x - (2/3) * 6 = 14
(2/3)x - 4 = 14
3) Add 4 to both sides of the equation:
(2/3)x - 4 + 4 = 14 + 4
(2/3)x = 18
4) Multiply both sides by 3 to eliminate the fraction:
3 * (2/3)x = 18 * 3
2x = 54
5) Divide both sides by 2 to solve for x:
(2x)/2 = 54/2
x = 27
Therefore, the solution to the equation is x = 27.